A Novel Z-Ring Associated Protein ZapA-Like Protein (PA5407) From Pseudomonas aeruginosa Promotes FtsZ to Form Double Filaments - Wang, Xiaoyu; Ma, Xueqin; Li, Zhe; Niu, Mingyue; Zhai, Meiting; Chen, Yaodong (Frontiers in Microbiology, 2021)
Bacterial cell division is initiated by the assembly of the contraction ring (Z-ring) which consists of the self-assembled FtsZ protofilaments and dozens of other associate proteins. ZapA, a regulatory protein found in almost all bacteria, stabilizes FtsZ protofilaments to form bundles and enhances the Z-ring condensation. Here, we reported that another small protein from Pseudomonas aeruginosa, ZapAL (PA5407), is a new FtsZ associated protein. ZapAL exists in many Pseudomonas species and shares only 20% sequence identity to ZapA. ZapAL interacts with FtsZ and induces FtsZ to form long straight double filaments; in comparison, ZapA promotes long bundles with multiple FtsZ filaments. ZapAL has only a mild effect on GTPase activity of FtsZ, which is reduced by around 26% when 10 µM ZapAL is added in the solution. However, to study their assembly dynamics using light-scattering assay, we found that FtsZ-ZapAL double filament is stable and no depolymerization process is observed, which is different from ZapA. Further research found that ZapA and ZapL are likely to form heterodimers. The bundles formed by the mixture of FtsZ-ZapA-ZapAL will depolymerize after GTP is hydrolyzed. Consistent with ZapAL interaction with FtsZ in vitro, the expression of ZapAL-GFP was observed as a narrow band or spots in the middle of the cells, suggesting that it is a component of bacterial division machinery. Similar to ZapA, ZapAL is also not essential for bacterial cell division. Little changes were observed when ZapAL gene was deleted, or overexpressed under normal conditions; however, overexpression of ZapAL caused zapA-deficient cells to grow approximately 2 times longer, showing a mild bacterial division defect. Although we still don’t know the exact physiological roles of ZapAL, our results suggest that ZapAL is a novel Z-ring associate protein, which may work together with ZapA to stabilize the FtsZ protofilament and Z-ring structure.